2003
DOI: 10.1080/02844310310001823
|View full text |Cite
|
Sign up to set email alerts
|

Spring-Mediated Cranioplasty Compared With the Modified Pi-Plasty for Sagittal Synostosis

Abstract: The aim of this study was to compare the safety, morphological outcome, and degree of parental satisfaction of the new spring-mediated cranioplasty with those of the modified pi-plasty in the management of sagittal synostosis. Ten patients with non-syndromic sagittal synostosis treated with the spring-mediated cranioplasty were followed prospectively. A control group of 10 sex-matched patients operated on with the modified pi-plasty procedure was chosen. Cephalometric radiographs were obtained preoperatively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 15 publications
1
42
0
Order By: Relevance
“…The initial postoperative CI of 75 or the 2-to 4-year postoperative CI of 73 was a good result, as compared with others. 2,4,6,12,15,18,22,23,[29][30][31][32]36,39,40,46,51 The decrease in CI that we observed over time is comparable to the limited available data on long-term outcome. 2,16 Adding a widening bridge complies with Fearon and colleagues' suggestion to overcorrect width to compensate for later growth restriction in that direction.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The initial postoperative CI of 75 or the 2-to 4-year postoperative CI of 73 was a good result, as compared with others. 2,4,6,12,15,18,22,23,[29][30][31][32]36,39,40,46,51 The decrease in CI that we observed over time is comparable to the limited available data on long-term outcome. 2,16 Adding a widening bridge complies with Fearon and colleagues' suggestion to overcorrect width to compensate for later growth restriction in that direction.…”
Section: Discussionsupporting
confidence: 70%
“…3,5,[9][10][11][12]15,17,[20][21][22][23][26][27][28][29][30][31][33][34][35][36]38,40,[43][44][45][46][47][48][49][50][51] The field continues to evolve and aims to reduce the impact of surgery. Minimally invasive approaches constitute the majority of recently detailed techniques.…”
mentioning
confidence: 99%
“…For this data set, only the papers providing total number, mean, and standard deviation of the relevant factors were included for statistical analysis. 8,16,22,25,27 The cranial index was collected preoperatively using CT scans to report the ratio of maximal biparietal distance over maximal occipitofrontal distance multiplied by 100. Postoperatively, cephalograms were used to obtain the biparietal distance and occipitofrontal distance of patients who had springs implanted for more than 2 months.…”
Section: Methods Data Collectionmentioning
confidence: 99%
“…Of those articles, 7 studies 3,4,8,17,22,25,27 were found that reported at least 5 cases of sagittal synostosis that were managed by SMC. The references of each paper were also reviewed to search for other relevant studies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation